HUBUNGAN POLA MAKAN TERHADAP STATUS GIZI PASIEN RAWAT JALAN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA RUMAH SAKIT GRANDMED LUBUK PAKAM - Raini Panjaitan; Reno Irwanto; Andreais Boffil Cholilullah; Salmi Angraini (JURNAL KESMAS DAN GIZI (JKG), 2021)
Diabetes mellitus is a chronic disease characterized by hyperlycemia. Risk factors for type 2 diabetes mellitus due to intake of carbohydrates, fats and protein. This study aims to see the relationship between diet in the nutrient status of type 2 diabetes mellitus in out patient in Grandmed Hospital Lubuk Pakam. This research method is an observational description with cross-sectional design. The sample is patients type 2 diabetes mellitus in out patient in Grandmed Hospital Lubuk Pakam. The sample is 30 people. The instruments are Food Recall 24 Hours and analyzed by nutrition app Nutri Survey. The data analysis used in this study was the Chi-Square test (95% CI) From the result of this research showed that 44,6% of patients with excess carbohydrate intake with a p value of 0.000 ≤ α (0,05). this research showed that 49,0% of patients with excess fat intake with a p value of 0.000 ≤ α (0,05). this research showed that 38,0% of patients with excess protein intake with a p value of 0.000 ≤ α (0,05). The conclusion are that there is significant relationship between diet in the nutrient status of type 2 diabetes mellitus in out patient in Grandmed Hospital Lubuk Pakam and type 2 diabetes mellitus in out patient nutrient status characteristics categorized as obesity.